Polycystic Ovarian Syndrome : Its Impact on Periodontal Disease - A.M. Sherene Christina Roshini1, E.Rajesh2 , N.Anitha3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Polycystic ovary syndrome (PCOS) is the common endocrine disorder among women of reproductive ageaffecting various health systems. This review literature explains pathophysiological mechanisms connectingPCOS and periodontal disease . Furthermore studies are needed to establish a clearer and stronger associationbetween the two disease.